The Influence of Photo Quality and Web3 Brand Image on Collector Purchase Intention Mediated by Collector Utilities Information on NFT Loka Masa Kompas - Fachruroji, Addien (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
In recent years, Non-Fungible Tokens (NFTs) have become a topic of discussion in society. NFTs have formed a new culture in the ownership of digital assets. The trading volume has increased, accompanied by the emergence of many creators in the local scene. With the significant opportunities recorded in this industry, many creator communities want to participate in presenting works that can be enjoyed by many people. By studying the variables of Web3 Brand Image and Photo Quality mediated by Collector Utilities Information on the Purchase Intention of prospective collectors in an NFT project, most of these variables have an influence, but one of them does not although it's not significant.